Analysis, Integration and Modeling of the Earth System (AIMES): Advancing the post-disciplinary understanding of coupled human–environment dynamics in the Anthropocene. (December 2015) - Schimel, David; Hibbard, Kathy; Costa, Duarte; Cox, Peter; Leeuw, Sander van der
Abstract: The IGBP Analysis, Integration and Modeling of the Earth System (AIMES) project has developed the notion of Earth System Science (ESS). ESS studies how the planet operates as a coupled system of interacting components, which produce emergent behaviors over and beyond the dynamics of the individual components. Many climate models used in the IPCC's 5th Assessment Report (AR5) include representations of the physical climate system and the biological components of the land and ocean carbon cycle. AIMES and its forerunner Global Analysis and Integration of Models (GAIM) helped lay the groundwork for this advance. Subsequently, AIMES has been instrumental in the evolution of climate models into Earth System Models, promoting dialog between the relevant communities to ensure greater consistency in the IPCC assessment process. Today, society faces interconnected challenges including climate change, financial crises, food security, governance of pandemics, and energy sufficiency. This requires decision makers to understand systemic risks for which the available tools provide insufficient guidance. AIMES is targeting to improve links of science with stakeholders in society to stimulate appropriate societal responses. Under Future Earth, AIMES prioritizes the understanding and modeling of human–environment interactions in the Anthropocene, focusing on gathering consistent data on biophysics and socioeconomics; lessons that can be learnt from past human–environment interactions; and the modeling of planet Earth as a complex system in which human beings are internal components rather than external actors. Key overarching themes include land-use change and the characterization and forecasting of critical transitions (or "tipping points") in the Earth System.